2014
DOI: 10.1007/s00204-013-1190-6
|View full text |Cite
|
Sign up to set email alerts
|

A 13-week repeated dose study of three 3-monochloropropane-1,2-diol fatty acid esters in F344 rats

Abstract: 3-monochloropropane-1,2-diol (3-MCPD), a rat renal and testicular carcinogen, has been reported to occur in various foods and food ingredients as free or esterified forms. Since reports about toxicity of 3-MCPD esters are limited, we conducted a 13-week rat subchronic toxicity study of 3-MCPD esters (palmitate diester: CDP, palmitate monoester: CMP, oleate diester: CDO). We administered a carcinogenic dose (3.6 × 10(-4) mol/kg B.W./day) of 3-MCPD or these esters at equimolar concentrations and two 1/4 lower do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 22 publications
3
44
0
1
Order By: Relevance
“…Recently, we also reported that oral administration of 3-MCPD by gavage causes cell death in the ductal epithelium of the initial segment of the epididymis in F344 rats (Onami et al, 2014b). In the present study, the degrees of epididymal damage were higher in F344 and lean rats than in fatty rats.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Recently, we also reported that oral administration of 3-MCPD by gavage causes cell death in the ductal epithelium of the initial segment of the epididymis in F344 rats (Onami et al, 2014b). In the present study, the degrees of epididymal damage were higher in F344 and lean rats than in fatty rats.…”
Section: Discussionsupporting
confidence: 66%
“…Although we have examined in vivo genotoxicity and subchronic toxicity of 3-MCPD and their esters in an ordinary rat model (Onami et al, 2014a(Onami et al, , 2014b, there is a further concern that 3-MCPD might exert more potent toxicity in human population with specific risk factor including hyperlipidemia. In addition, it has been demonstrated that obesity is closely associated with risk for chronic disorders of kidney, one of the target organs of 3-MCPD toxicity (Chen et al, 2004;Ejerblad et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…3-MCPD dipalmitate (equivalent to 10.34 mg/kg b.w. 3-MCPD) for 90 days did also not induce histopathological changes, but slightly elevated organ weight of the kidneys in a very recent study (Onami et al 2014b). By contrast, much higher doses also applied in the two aforementioned studies exerted histopathological effects (Li et al 2013;Onami et al 2014b), and administration of a high dose of 40 mg/kg b.w.…”
Section: Namesmentioning
confidence: 84%
“…3-MCPD) for 90 days did also not induce histopathological changes, but slightly elevated organ weight of the kidneys in a very recent study (Onami et al 2014b). By contrast, much higher doses also applied in the two aforementioned studies exerted histopathological effects (Li et al 2013;Onami et al 2014b), and administration of a high dose of 40 mg/kg b.w. 3-MCPD or an equimolar 3-MCPD diester dose reduced eosinophilic bodies in the renal proximal tubular epithelium after 4 weeks of exposure (Onami et al 2014a).…”
Section: Namesmentioning
confidence: 84%
See 1 more Smart Citation